Інтертекстуальні особливості використання євангельського сюжету життєписною прозою межі ХХ−ХХІ ст. - Акіншина, Ірина; Akinshyna, Iryna (Волинський національний університет імені Лесі Українки, 2008)
Наголошено на виділенні в останні роки специфічної категорії творів, які слід вважати художньо-біографічними тільки умовно. Це життєписи біблійних персонажів. Авторка аналізує українські художні життєписи в контексті аналогів світової літератури. The respondent emphasises on marking out of specific writing category during last years, which should be treated as belles-biographic only conditionally. These are biographies of biblical characters. The author analyses and compares works of ukrainian writers in contexts world-wide literature.
The Intertextual Features of Using of Evangelic Subject by the Biographic Prose on the Border of the XX−XXI Century
Keywords: художньо-біографічна література; belles-biographical literature; євангельський сюжет; evangelic subject; інтертекст; intertext